Dampak Implementasi Aritificial Intelligent Pada Sektor Pendidikan. - Risna Oktaviati (Advances In Education Journal, 2025)
The rapid advancement of Artificial Intelligence (AI) technology has significantly transformed various sectors, including higher education. This study aims to systematically review the impacts and implications of AI implementation within academic environments using a Systematic Literature Review (SLR) approach. The findings reveal that AI contributes positively to personalized learning, administrative efficiency, and predictive analytics for identifying students at academic risk. However, the implementation of AI also presents notable challenges, including ethical concerns, data privacy issues, unequal access to technology, and potential overreliance on automated systems. This study recommends the development of clear institutional policies, AI literacy programs for educators and students, and the integration of AI systems that uphold pedagogical values. This review is expected to serve as a reference for formulating inclusive, ethical, and sustainable strategies for the use of AI in higher education.